2022
DOI: 10.3390/app13010268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Magnetic Field Generated by a New NeFeB Cover Screw on Bone Healing around Endosseous Implants: A Case Series Report from Dental Practice

Abstract: This study aimed to investigate the effect of static magnetic field (SMF) generated by innovative cover screws made of NeFeB on early bone healing around dental implants. The study was carried out on humans in a private dental practice. Eight 3i implants (Biomet, Palm Beach, FL, USA) were placed in the posterior mandible at 3.6 and 3.7. The control implants were closed with a conventional screw (G1), while the test implants were closed with a Supercharged® screw (G2). Both groups were compared for stability at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The growing interest in the application of magnetic fields in bone metabolism in order to facilitate its maturation has been well highlighted in various scientific papers. In particular, in dentistry to favour implant osteointegration and slow down crestal resorption around the implant itself [ 29 , 30 , 31 ], as well as to promote the maturation of multipotent cells in order to cure periodontal disease in the future [ 32 ]. Moreover, the application of magnetic fields is being applied in the study of bone-tissue growth in order to evaluate the cell–cell and cell–extracellular matrix interaction [ 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing interest in the application of magnetic fields in bone metabolism in order to facilitate its maturation has been well highlighted in various scientific papers. In particular, in dentistry to favour implant osteointegration and slow down crestal resorption around the implant itself [ 29 , 30 , 31 ], as well as to promote the maturation of multipotent cells in order to cure periodontal disease in the future [ 32 ]. Moreover, the application of magnetic fields is being applied in the study of bone-tissue growth in order to evaluate the cell–cell and cell–extracellular matrix interaction [ 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of magnetic fields has been applied in orthodontics (movement of the teeth) and prosthodontics (maxillofacial prosthesis and in overdentures) [ 28 ] and in implantology with the purpose of improving osteointegration [ 29 , 30 , 31 ]. Moreover, the possible application of the magnetic field for the treatment of periodontal disease is currently being studied [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…the Once healing has occurred, we move on to the second phase characterized, however, by the surgical exposure of the implant to proceed with the incorporation of the abutments in order to optimize prosthetic rehabilitation. [18][19][20][21] . In another studies Author show that it could be right the use of photobiomodulation for improve the bone healing.…”
Section: Introductionmentioning
confidence: 99%
“…These types of results have led some researchers, in particular Simion et al [32,33], to go back to machined implants, without treatment. In the literature, there have been some interesting works on the improvement of the osteoblastic response obtained without altering the bone surface, but only by using particular cap screws for implants equipped with static magnetic fields [34][35][36][37]. The static magnetic fields according to these studies have been demonstrated, both in vitro and in vivo, to increase osteoblast differentiation and increase bone matrix deposition.…”
Section: Introductionmentioning
confidence: 99%